Dystocia Due to Dicephalus Fetal Monster in a Buffalo - Balu Naik M; Udaya Kiran A; Sonia Banisetty (The Indian Veterinary Journal, 2026)
This case report documents a rare case of dystocia caused by a dicephalus fetal monster in a buffalo. Vaginal examination revealed a fully dilated cervix and a dead fetus with duplicated heads in anterior presentation. The fetus was delivered per-vaginum by lubrication and obstetrical manoeuvre with uneventful recovery of the dam.